Economic impacts of illegal, unregulated and unreported fishing activities on artisanal fishing in Somalia - Jama, Ahmed Khadar Abdi; Ariffin, Muhammad Irwan; Abdullah Yusof, Selamah (Adonis & Abbey Publishers, 2022)
This study aimed to examine the economic impacts of illegal, unregulated, and unreported (IUU) fishing on Somali artisanal fishermen. This study employed the systematic random sampling, using the quantitative research method; it administered survey questionnaire to 282 samples of Somali artisanal fishermen. The study found that, on average, each fisherman was attacked four times over a five-year period (2015–2019), thus negatively affecting the local fishermen’s sources of livelihood. In addition to the loss and damage of the fishing equipment, the study found that IUU fishing reduced their fish catch, the number of fishing crew, and investment in fishing. It also caused an increase in the overall cost of fishing. Based on findings, the study made a valuable contribution to this field of study on the fisheries sector by providing a detailed analysis on the nature and extent of the economic impacts of IUU fishing that is relevant for all policy makers involved in developing Somalia’s fishing sector.